Multimedia games for elementary/primary school education and entertainment - Laghos, Andrew (My University, 2010)
Computers are increasingly being used as educational tools in elementary/primary schools worldwide. A specific application of such computer use, is that of multimedia games, where the aim is to combine pedagogy and entertainment. This study reports on a case-study whereby an educational multimedia game has been developed for use by elementary school children. The stages of the application’s design, implementation and evaluation are presented. Strengths of the game are identified and discussed, and its weaknesses are identified, allowing for suggestions for future redesigns. The results show that the use of games can engage children in the learning process for longer periods of time with the added benefit of the entertainment factor.
Keywords: Computers--Study and teaching (Elementary); Computer games; Career education--Computer-assisted instruction